PROMOTION ON THE INTERNET AS A FUNCTION OF AGRIBUSINESS DEVELOPMENT IN CENTRAL SERBIA - Dejan Dašić; Milijanka Ratković; Anđela Marčetić; Miloš Tošić (Ekonomika Poljoprivrede (1979), 2023)
The advancement of information technologies during the past several decades has excelled, especially those that are applicable to all aspects of human activity. The aim of this paper is to determine the views of agricultural product producers in Central Serbia on e-business, with a focus on determining the perception of the promotional potential of the Internet itself. As social media networks, play an increasing role in e-business globally, the intention is to emphasize the importance of their use in order to promote various agricultural and food products. The survey included a final sample of 92 respondents. The basic hypothesis in this paper is that the Internet as an e-business technology has great potential for improving the position of farmers and producers, but also that it is not used in its full potential. The results confirm the aforementioned hypothesis, while the conclusions are directed towards the necessity of education in order of getting to know the benefits of e-business, as well as the advantages of promotion via social networks.